CO2 intensity and GDP per capita. Issue 2 (1st November 2019) - Hannesson, Rögnvaldur
Abstract : Purpose: To investigate whether CO2 intensity falls at a diminishing rate as countries grow richer. Design/methodology/approach: Regression of CO2 intensity on the gross domestic product (GDP) per capita, including squared and cubic terms, for a panel of countries and individual countries. Findings: CO2 intensity falls at a diminishing rate as countries grow richer. Originality/value: Many studies have found that CO2 intensity falls with GDP per capita, but whether it does so at a diminishing rate has not been investigated. This result suggests that structural changes in GDP (more services) as countries get richer will provide little or no help toward decarbonization. It is shown that the extraction of minerals critical for industrial production has increased on par with real GDP. This could explain why CO2 emissions fall at a diminishing rate.